Strategic management paper for International SOS (Phils.), Inc. - Mediano, Hermalyne B. (Animo Repository, 2007)
The Financial Services Industry has kept afloat despite the unfavorable events such as unstable peace and order in the country that threatened domestic stability and the September 11, 2001 terrorist attack in the Word Trade Center, New York, where billions of premiums has been paid that has created a stiff competition in the industry worldwide. It continuously shows signs of development, which may not be remarkable but still something to be pleased about. Although the changes are modest, the underlying pace of reform in the Insurance industry has been making progress quickly. This translates to a fast changing business environment where oftentimes, only the companies that were able to create value to the customers survived. The most encompassing, most significant and most difficult challenge that confronts any business organization is how to lay the foundation for tomorrow's success while competing to win in today's marketplace. International SOS (Phils.), Inc. is facing tough competition against other assistance providers. It needs more than just commitment, dedication and conscious efforts in order to survive. Rather, the company must continuously improve to win in the marketplace and create new ways to configure the organization to cope with changing environments. To compete and move towards its vision of being the number one assistance company in the Philippines, it is proposed that the company pursue the following strategies: Strengthen current alliance with insurance, banks, credit cards, oil and gas companies. Increase the level of quality assurance and reliability to customers by creating a service oriented environment throughout the company. Invest on online advancements for Philippine operations. The above proposed strategies intend to achieve the following objectives: 1. Improve net income by 5% annually for the next 5 years. 2. Increase member base of the company to an average of 5% growth per year from 2008 2012 on the assumption that the industry grows on the average of 10% every year. The proposed functional strategies include among others the following: 1) Embark in marketing campaign to targeted companies. 2) Implement an investment policy geared towards maximization of yield on investments. 3) Periodically assess the existing system and perform studies on the use of latest available technology that may be beneficial to the company. 4) Implement a comprehensive training and development program to ensure continuous education and personal development of employees. 5) Establish a system of reward and recognition for excellent employee performance. International SOS (Phils.), Inc should come up with the suitable rewards for excellent performance. This may be in the form of merit increases, bonuses, privileges, recognitions, etc.